O planejamento territorial participativo do Pará e o processo de formulação, implementação e tomada de decisões de políticas públicas: inovação e limites para a democracia participativa - MESQUITA, Thiago Broni de (Universidade Federal do Pará, 2014)
By taking the state government of Pará in 2007, the then Governor Ana Julia Carepa (PT) presents the Participative Territorial Planning which was an instrument through which the Government of the State of Pará aimed to ensure popular participation and decentralization of management, through steps where the population was consulted on issues and public policy proposals advocated local or regional. These proposals were incorporated into the statutory planning instruments (PPA, LDO, LOA) for the government to implement over the 04 years of management. The process involved the participation of more than 80,000 people across the state and elected councilors to compose 3983 12 Regional Councils of Popular Participation and more Counselors State 105 to compose the State Board of Public Participation. However, the project worked on actors with veto power within the executive branch, who ultimately decided not to implement public policy through the PTP, due to interests and infighting in the government. Thus this thesis aims to analyze the factors that have prevented the action of the PTP, making the process ineffective during the years 2007 and 2010.